The Contributive Roles of Bilingualism in English Language Teaching - Rama Dwika Herdiawan (Journal of English Language Learning, 2017)
AbstractThis study is aimed to explore what the contributions of bilingualism to the English language teaching are as well as how the teachers employed it in their instructional processes. This also deals with how the students were engaged in  the process. This study employed qualitative research which focused on using interpretative design involving the classroom observation and also semi-structured interview. The result of the study revealed that the roles of bilingualism were considered to be a prominent tools which fostered the students’ communicative competence as well as the way the teachers taught the material. In conclusion, the implementation of bilingualism has significant roles in terms of teaching and learning the target language (L2) at junior high school level.Keywords: Bilingualism, English Language Teaching, Communicative Competence